2016
DOI: 10.1152/ajpheart.00666.2015
|View full text |Cite
|
Sign up to set email alerts
|

Brief serotonin exposure initiates arteriolar inward remodeling processes in vivo that involve transglutaminase activation and actin cytoskeleton reorganization

Abstract: LA. Brief serotonin exposure initiates arteriolar inward remodeling processes in vivo that involve transglutaminase activation and actin cytoskeleton reorganization. Am J Physiol Heart Circ Physiol 310: H188 -H198, 2016. First published November 11, 2015; doi:10.1152/ajpheart.00666.2015.-Inward remodeling of the resistance vasculature is strongly associated with life-threatening cardiovascular events. Previous studies have demonstrated that both actin polymerization and the activation of transglutaminases medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…Fourth, findings from the ex vivo treatment of arteries or cells with adropin for 24 hours suggest that adropin-induced de-stiffening effects can occur rather quickly. The acute nature of these adropin effects is consistent with the idea that cytoskeletal remodeling can occur rapidly (i.e., within minutes/hours) (207,(221)(222)(223); nevertheless, time course studies are needed to establish the kinetics of these changes. Fifth, follow-up telemetry studies are needed to determine if the observed changes in arterial stiffness in our mouse model of adropin deficiency and/or adropin treatment are associated with, or independent of, changes in blood pressure.…”
Section: Discussionsupporting
confidence: 66%
“…Fourth, findings from the ex vivo treatment of arteries or cells with adropin for 24 hours suggest that adropin-induced de-stiffening effects can occur rather quickly. The acute nature of these adropin effects is consistent with the idea that cytoskeletal remodeling can occur rapidly (i.e., within minutes/hours) (207,(221)(222)(223); nevertheless, time course studies are needed to establish the kinetics of these changes. Fifth, follow-up telemetry studies are needed to determine if the observed changes in arterial stiffness in our mouse model of adropin deficiency and/or adropin treatment are associated with, or independent of, changes in blood pressure.…”
Section: Discussionsupporting
confidence: 66%
“…While progress has been made in following actin polymerization in small blood vessels (Foote et al . ), this is not yet suitable for measurement of depolymerization which would have been required for the present study.…”
Section: Discussionmentioning
confidence: 95%
“…However, this is the first report showing that diet induced obesity is associated with enhanced EnNaC expression, and that this is prevented XO inhibition. The activation of EnNaC results in polymerization of G- to F-actin [30]. This results in decreased flow-mediated NO production due to disruption of the endothelial glycocalyx (i.e., surface layer comprising a complex of glycoproteins located on the luminal surface of EC) and its interaction with endothelial nitric oxide synthase (eNOS) during flow-mediated vasodilation [31].…”
Section: Discussionmentioning
confidence: 99%